Fabrication and properties of PZT-cement-encapsulated carbon composites - Arnon Chaipanich (2018)
Lead zirconate titanate, Pb(Zr0.52Ti0.48)O 3 (PZT) has excellent piezoelectric properties and has been used in a number of applications such as sensors and actuators. Recently, PZT has been used with a cement based material to produce new types of composite. These new piezoelectric-cement based composites have been developed for sensor applications in civil engineering works where these composites would provide better matching to concrete than the existing normal piezoelectric ceramic or piezoelectric-polymer composites. In this work, encapsulated carbon addition of 2% by volume was added to the PZT-cement composites using pressed-cured method. Dielectric properties of the composites were investigated from 1 to 100 kHz as a preliminary investigation. The results show that the dielectric constant was found to be higher for the composite with the addition of encapsulated carbon. The dielectric loss of the composite with the encapsulated carbon, however, was found to be less when compared to the composite with no encapsulated carbon. Scanning electron micrographs of these composites also revealed that a dense microstructure can be obtained from this method. © (2010) Trans Tech Publications.